The importance of the internal audit in a company. The differences between internal and extermal auditing - Galynska, Olena; Manuilova, Аnactasia (My University, 2014)
The thesis describes the principles and tasks of internal and external auditing, defines their main types, similarities and differences.У тезах описано принципи і завдання внутрішнього і зовнішнього аудиту, визначено їх основні типи, подібності та відмінності
Keywords: internal auditing; external auditing; auditor’s tasks; principles of auditing; внутрішній аудит; зовнішній аудит; принципи аудиту; завдання аудитора; внутренний аудит; внешний аудит; принципы аудита; задание аудитора; кафедра ділової іноземної мови та міжнародної комунікації